History of emotions : insights into research = Geschichte der Gefühle : Einblicke in die Forschung - Max-Planck-Institut für Bildungsforschung - Forschungsbereich Geschichte der Gefühle; Max-Planck-Gesellschaft zur Förderung der Wissenschaften (2013)
Online-Portal; the provider of this website within the legal meaning of the term is the registered association Max Planck Soc. for the Advancement of Science